ANALYTICAL ROLE OF BARDAK'S WORK IN INCREASING THE SCIENTIFIC AND SPIRITUAL POWER OF YOUTH (Conference Zone, 2021)
The article discusses the scientific, spiritual and educational significance of the study of Berdak's epics in the literature of the Karakalpak people.